The Influence of Food and Beverage Product Marketing on Consumer Purchase Interest in MSME Actors in Makassar - Naim, Rezky; Sultan; ST. Rukaiyah; Rahmat Laan (Yayasan Cita Cendikiawan Al Kharizmi, 2023)
The purpose of this study was to examine the effect of food and beverage variables on purchasing preferences. Data collection was carried out by distributing questionnaires to MSME stakeholders in five sub-districtsspread across the city of Makassar. Hypothesis testing here involves the use of multiple regression analysis. The results of this study show that food and beverage variables have a strong effect on purchase intent.Background: Buying interest in consumers is a very important phenomenon in marketing activities. Buying interest is consumer behavior that bases the purchase decision to be made